Maternal and fetal outcomes in pregnancies complicated by Marfan syndrome. Issue 22 (25th May 2019) - Cauldwell, Matthew; Steer, Philip J; Curtis, Stephanie L; Mohan, Aarthi; Dockree, Samuel; Mackillop, Lucy; Parry, Helen M; Oliver, James; Sterrenberg, Monique; Wallace, Suzanne; Malin, Gemma; Partridge, Gemma; et al.
Abstract : Objectives: Information to guide counselling and management for pregnancy in women with Marfan syndrome (MFS) is limited. We therefore conducted a UK multicentre study. Methods: Retrospective observational study of women with MFS delivering between January 1998 and March 2018 in 12 UK centres reporting data on maternal and neonatal outcomes. Results: In total, there were 258 pregnancies in 151 women with MFS (19 women had prior aortic root replacements), including 226 pregnancies ≥24 weeks (two sets of twins), 20 miscarriages and 12 pregnancy terminations. Excluding miscarriages and terminations, there were 221 live births in 139 women. Only 50% of women received preconception counselling. There were no deaths, but five women experienced aortic dissection (1.9%; one type A and four type B—one had a type B dissection at 12 weeks and subsequent termination of pregnancy). Five women required cardiac surgery postpartum. No predictors for aortic dissection could be identified. The babies of the 131 (65.8%) women taking beta-blockers were on average 316 g lighter (p<0.001). Caesarean section rates were high (50%), particularly in women with dilated aortic roots. In 55 women, echocardiographic aortic imaging was available prepregnancy and postpregnancy; there was a small but significant average increase in AoR size of 0.84 mm (Median follow-up 2.3 months) Conclusion: There were no maternal deaths, and the aortic dissection rate was 1.9% (mainly type B). There with no identifiable factors associated with aortic dissection in our cohort. Preconception counselling rates were low and need improvement. Aortic size measurements increased marginally following pregnancy.